Effect of Nartogra stim, a Recombinant Human Granulocyte Colony-stimulating Factor on Elastase-induced Emphysema in Rats - Yoshimatsu, Akiko; Nan-ya, Ken-ichiro; Miki, Ichiro (Arzneimittelforschung, 2009)
Granulocyte colony-stimulating factor (G-CSF) is known to mobilize stem cells to various organs and that it participates in tissue regeneration. Effect of the recombinant human G-CSF nartograstim (CAS 134088-74-7) was tested on elastase-induced emphysema. Porcine pancreas elastase (PPE) was administered intratracheally to male Sprague-Dawley rats to induce parenchymal destruction which was assessed by measuring the mean linear intercept (Lm) in tissue sections as an indicator of air space size. Lung alveoli were destructed and Lm value was significantly increased 2 weeks after PPE instillation. Increase in Lm was sustained for 8 weeks after PPE instillation. Two weeks after PPE instillation, 100 and 200 µg/kg of G-CSF injected for 5 d, followed by once and 3 injections a week for 5 weeks had reversed the increase in Lm by 28.7% (P = 0.02) and 35.2% (P = 0.004), respectively. Coadministration of 100 µg/kg × 5 injection of G-CSF with all-trans-retinoic acid (ATRA; 3 mg/kg/d) for 3 weeks from 2 weeks after PPE instillation significantly inhibited the increase in Lm by 36% (p < 0.01), whereas administration of G-CSF or ATRA alone did not produce significant improvement. Preventive administration of G-CSF, which was treated for 4 weeks from 4 days after PPE instillation, did not improve enlargement of Lm. These data indicate that the administration of G-CSF is beneficial for the recovery of destructed alveoli.
Keywords: CAS 134088-74-7; Emphysema; G-CSF; Granulocyte colony-stimulating factor; Nartograstim; all-trans-Retinoic acid; Tissue regeneration